PENGARUH PELAYANAN PRIMA TENAGA ADMINISTRASI PENDAFTARAN TERHADAP KEPUASAN PASIEN DI UNIT RAWAT JALAN RSUD ARIFIN ACHMAD PROVINSI RIAU - Firdaus, Muhammad; Huljannah, Angela; Tonis, Marian; Suryandartiwi, Wiwik (Journal of Hospital Administration and Management (JHAM), 2023)
Excellent service is very good or best service to patients based on quality standards to meet the needs and desires of patients so that patients can get satisfaction. Satisfaction is the level of one's feelings after comparing the perceived performance or results with their expectations. So the level of satisfaction is a function of the difference between perceived performance and expectations. The purpose of this study was to determine the effect of Excellent Service by Registration Administration Personnel on Patient Satisfaction in the Outpatient Unit at Arifin Achmad Hospital, Riau Province. This study used a Quantitative Research Type with the Cross Sectional Study Method which was carried out at Arifin Achmad Hospital, Riau Province. This research was conducted by distributing questionnaires with 100 respondents, namely outpatients at RSUD Arifin Achmad, Riau Province. The results of this study were obtained from research data processing which showed that the influence of excellent service by registration administration personnel had a significant effect on patient satisfaction in the outpatient unit at RSUD Arifin Achmad, Riau province. This can be seen by the sig value of 0.000 <0.005 while the results of the T test show that the indicators of attitude, ability, attention, action, accountability, and appearance simultaneously affect patient satisfaction. Then R2 produces 0.487, this means that 48.7% of the variation in patient satisfaction can be explained by 6 indicators of excellent service, namely attitude, ability, attention, action, accountability, and appearance, while the remaining 51.3% is influenced by other factors outside the variables.